CASE STUDY OF KARIYA TRADITION IN FORMING THE CHARACTER OF FEMALE TEENS - Ismail, Ismail; Mondong, Tonny Iskandar; Hasan, Renol (Satmata: Journal of Historical Education Studies, 2025)
This study aims to determine how the existence of the kariya tradition in the Muna community in Parigi Village and how the implications of kariya values as character education for adolescent girls in Parigi Village. This study uses a qualitative method using a descriptive approach that describes to describe the existence of the kariya tradition in the Muna community in Parigi Village and describes the implications of kariya values as character education for adolescent girls in Parigi Village. So that in collecting data in this study, namely through Observation which focuses on direct observation in the field, interviews and documentation with traditional shops who know about the origins of the kariya tradition. Documentation as a step in data collection, it is necessary to document various activities during the process of carrying out the kariya tradition ritual. The results of this study indicate that; First, the existence of the kariya tradition as character education for adolescent girls in Parigi Village is still being carried out until now, even with various changes that exist. The two implications of character education values in the kariya tradition can be described in several processions, including kafoluku containing the value of self-recognition, kabhansule the value of understanding the role of women in community life, katandhono wite containing the value of building humility and responsibility, and linda the value of self-actualization and the importance of aesthetic values.